Investigating the volatile and non-volatile metabolites in soy cheese fermented with Lactiplantibacillus pentosus during gel formation and cold storage - Fatemeh Rahmani; Ali Moayedi; Victor Dopazo; Giuseppe Meca; Morteza Khomeiri; Mahboobeh Kashiri (Food Chemistry: X)
Undesirable sensory properties are regarded as the main obstacle to developing soy-based products. This study aimed to apply lactic acid bacteria to improve soy cheese's sensory and nutritional aspects. Lactiplantibacillus pentosus was used to coagulate soy milk as an alternative to Glucono-delta-lactone (GDL). The changes in pH, viable cell count, aroma profile, Gamma-aminobutyric acid (GABA) content, and organic acids were determined during gel formation and cold storage. L. pentosus grew well in soy milk and caused coagulation within 6 h. The aroma analysis by gas chromatography with a single-quadrupole/mass spectrometer detector-headspace solid-phase microextraction (GC/MS-SPME) showed a reduction in green and beany flavor, while generating pleasant volatiles during fermentation and storage. Significant variation in Lactate, Acetate, and GABA was found among the samples and storage time. Fermentation with L. pentosus was found to be a promising approach to manufacture a novel soy cheese with a desirable aroma and nutritional potential.